From tai chi practice to microcirculation improvement : potential mechanisms and research prospects - Chen, Zaihao; Li, Cuihan; Zhang, Jianwei; Lyu, Shaojun (The Journal of the International Society of Chinese Health Practices, 2025)
Abstract: Background: Microcirculation is the ultimate organ of the cardiovascular system. It is a complex and heterogeneous network composed of terminal arterioles, capillaries and venules connecting arteries and venous systems. As the end of the circulatory system, it is also the main place for the exchange of nutrients and oxygen in the blood. Tai Chi movement has the characteristics of spiral expansion and rotation, and in the process of practice, it advocates ' guiding qi with meaning and transporting body with qi '. The body is relaxed and quiet, reaching the tip of the hand and foot, which can smooth qi and blood. Famous doctors of traditional Chinese medicine believe that qi and blood are closely related. Therefore, Tai Chi exercise is closely related to human microcirculation. Objective: This study mainly reviews the positive effects of Taijiquan practice on microcirculation, discusses the possible mechanism of Taijiquan practice microcirculation, and looks forward to the future research direction. Methods: Using the method of literature, through the keywords “Tai Chi”, “microcirculation”, “microvessel”, “hemodynamics”, “hemorheology”, “transcutaneous oxygen partial pressure”, “regulation mechanism” and other keywords in the CNKI database, Wanfang database, Pubmed database, Web of Science database search related literature, for Tai Chi practice to improve the role of microcirculation, and its potential regulatory mechanism, to provide theoretical support. Results: 1.Tai Chi affects microcirculation in four aspects (1)In terms of vascular morphology, taijiquan exercise improves microvascular morphological abnormalities (2) Based on the perspective of hemodynamics, Tai Chi exercise improves microvascular reactivity and enhances blood perfusion (3) Based on the perspective of hemorheology, taijiquan exercise reduces blood viscosity and promotes blood circulation (4) Tai Chi exercise improves transcutaneous oxygen partial pressure and improves oxygenation capacity. 2.Microcirculation regulation mechanism : The mechanism of exercise regulating microcirculation is diversified : (1) Promote the increase of angiogenesis factor VEGF to lead to capillary growth, improve the microvascular network, and reduce vascular resistance (2) Cause the balance of factors affecting vasoconstriction and dilation, such as prostacyclin and thromboxane (3) Reduce oxidative stress, enhance antioxidant capacity, and improve redox environment (4) Promote the balance of sympathetic and parasympathetic systems in the autonomic nervous system, reduce sympathetic activity, and enhance parasympathetic activity (5) Reduce pro-inflammatory cytokines, enhance anti-inflammatory factors, and improve the balance of pro-inflammatory and anti-inflammatory. (6) Enhanced NO release, enhanced endothelium-dependent relaxation ability. (7) Enhance hemodynamic changes and increase shear stress. The mechanism of microcirculation regulation by exercise is more complex and diverse, and multiple mechanisms may be involved in the process of regulating microcirculation. The mechanism of Tai Chi may affect microcirculation: (1) Tai Chi exercise improves microcirculation by increasing NO content and enhancing vasodilation. (2) Tai Chi exercise improves microcirculation by reducing inflammatory factors serum interleukin and tumor necrosis factor. (3) Tai Chi exercise improves autonomic nerve balance and improves microcirculation. (4) Tai Chi exercise enhances antioxidant capacity to improve microcirculation. Conclusion: 1. Evidence-based research on Tai Chiexercise to improve microcirculation has achieved initial results, but it is necessary to strengthen its own system theory or perspective research, and lack of Tai Chi mechanism such as TCM syndrome differentiation and five elements. At present, the research on the mechanism of Tai Chi regulating microcirculation is diversified, such as nerve regulation, anti-inflammatory, anti-oxidation regulation, vasoconstriction and relaxation regulation, but the research on the mechanism of Tai Chi promoting microcirculation regulation still needs to be expanded, and the research on key molecules needs to be expanded. The regulation mechanism requires a combination of points and lines to form a regulation path paradigm.